Women’s Rights Laws in Pakistan: Challenges and Solutions - Gondal, Abdul Qayyum; Hatta, Zulkarnan (Annals of Human and Social Sciences, 2024)
Women’s rights in Pakistan have been a focal point of national and international discourse for decades. Despite significant legislative advancements, including the Protection of Women against Violence Act (2016) and the Anti-Rape Ordinance (2020), Pakistani women continue to face substantial barriers to equality and justice. Main objective of this research is to explore the state of women’s rights laws in Pakistan, focusing on the challenges and potential solutions for improving gender equality and protection for women. Its historical review analyzes the intersection of national legislation and international human rights norms, highlighting persistent challenges faced by women. This study employs a qualitative research design to explore the challenges and solutions related to women’s rights laws in Pakistan. The research involve a combination of primary and secondary data collection methods to provide a comprehensive understanding of the subject. Semi-structured interviews with stakeholders, such as lawmakers, solicitors, and schematic survey of society norms provide a broad results of women rights laws in Pakistan. Results analysis show Key challenges like cultural and societal norms, inadequate implementation and enforcement of laws, and limited awareness and education regarding women’s rights. Furthermore, it proposes solutions to enhance the impact of women’s rights laws in Pakistan. By addressing these issues, Pakistan can move towards a more equitable society where women’s rights are fully realized and protected.